Assessment of different methods for diagnosing dental caries in epidemiological surveys - Assaf AV, Meneghim MC, Zanin L, Mialhe FL, Pereira AC, Ambrosano GMB. (Blackwell Synergy, 2004)
The aims of the study were: (i) to assess different clinical diagnostic methods of dental caries during epidemiological surveys; (ii) to determine which combinations of methods and diagnostic adjuncts show the best performances in epidemiological surveys when compared with examinations performed in a traditional dental setting (standard); (iii) to evaluate the influence of including noncavitated (NC) lesions in dental caries estimation.